Corrigendum to ‘Predictors of ASDAS-CRP inactive disease in axial spondyloarthritis during treatment with TNF-inhibitors - Ørnbjerg, Lykke M. (2023)
The authors regret that the following incorrect values have been published in the original paper: In the abstract: Line 11-12: “age, per year: 0.97 (0.97-0.98)” should be “age, per year: 0.98 (0.97-0.99)” Line 12: “men vs. women: 1.88 (1.60-2.22)” should be “men vs. women: 1.79 (1.51-2.12)” Line 12: “current vs. non-smoking: 0.76 (0.63-0.91)” should be “current vs. non-smoking: 0.72 (0.59-0.87)” Line 12-13: “HLA-B27 positive vs. negative: 1.51 (1.20-1.91)” should be “HLA-B27 positive vs. negative: 1.65 (1.27-2.15)” Line 14: “CRP>10 vs. ≤10 mg/l: 1.49 (1.25-1.77)” should be “CRP>10 vs. ≤10 mg/l: 1.36 (1.14-1.62)” Line 15-16: “fatigue and spinal pain: 0.99 (0.99-1.00) and 0.99 (0.99-1.99)” should be “fatigue and spinal pain: 0.99 (0.99-0.99) and 0.99 (0.99-1.00)” In Table 3, row with EPV (row 3 after header/subheader): Column with header/subheader “Czech Republic/ATTRA”: EPV 15.9 should be 13.2 Column with header/subheader “Netherlands/ARC”: EPV 1 should be 1.0 Column with header/subheader “Portugal/Reuma.pt”: EPV 14.7 should be 13.1 Column with header/subheader “Romania/RRBR”: EPV 2.8 should be 2.4 Column with header/subheader “Turkey/TURKBIO”: EPV 12.9 should be 11.8 In Table 5, row with “Patient global score, mm” (row 10 counting from row with “Age at treatment start, years”): In the column with header: “Analysis of 12-month drug retention” and subheader: “Univariate”, the value for the odds ratio (OR) is missing. The OR should be 0.99. The authors would like to apologise for any inconvenience caused.